Is platelet activating factor (PAF) an important mediator in bronchial asthma? - R. H. Gundel; H. O. Heuer; L. G. Letts (Mediators of Inflammation)
The development of selective PAF receptor antagonists may provide a novel approach to the treatment of human bronchial asthma. In preclinical animal models of human asthma, PAF receptor antagonists have been found to be efficacious in blocking antigen-induced changes in lung function. However, the majority of these models involve acute inflammatory events and transient changes in lung function and, therefore, their relevance to human asthma is questionable. In a recent study with a primate model of chronic airway inflammation and hyperresponsiveness, we have shown that treatment with a PAF receptor antagonist had no effect on reducing chronic inflammation and hyperresponsiveness. Similarly, recent studies in human asthmatics with PAF receptor antagonists have failed to show efficacy in blocking allergen-induced airway responses or to have any steroid sparing effects in patients with ongoing asthma. Thus, it seems that PAF may not be a key mediator which can be blocked and thereby provide therapy for bronchial asthma.